Promotion Development through Online Media and Client Data Base Management at PT Tetrahiel Professional Management - Saputra, Riski Adi; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2024)
The rapid changes in the global business environment demand quick adaptation to technological and regulatory shifts. Management consulting firms like PT Tetrahiel Profesional Manajemen in Yogyakarta assist businesses in navigating these challenges with services in financial, HR, marketing, and information systems consulting, plus training programs. This internship optimized PT Tetrahiel's online promotion and client database management. Activities included digital marketing training via Instagram and TikTok, developing SOPs for client acquisition and follow-up, and creating a computerized client database using Excel. These initiatives enhanced marketing efficiency, streamlined client acquisition, and organized client information, boosting PT Tetrahiel's operational effectiveness and market presence.